2014
DOI: 10.1007/s00420-014-0971-4
|View full text |Cite
|
Sign up to set email alerts
|

Whole-body vibration and the risk of low back pain and sciatica: a systematic review and meta-analysis

Abstract: This review shows that there is scientific evidence that exposure to WBV increases the risk of LBP and sciatica.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
90
2
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(99 citation statements)
references
References 77 publications
3
90
2
4
Order By: Relevance
“…In the same analysis, a summary POR of 1.67 (95% CI 1.25-2.23) was found for 12-month prevalence of sciatic pain in the professional drivers. Earlier meta-analyses have similarly found an excess risk of LBP and sciatic pain in professional drivers [42,58,59,60].…”
Section: Low Back Pain and Sciaticamentioning
confidence: 86%
See 1 more Smart Citation
“…In the same analysis, a summary POR of 1.67 (95% CI 1.25-2.23) was found for 12-month prevalence of sciatic pain in the professional drivers. Earlier meta-analyses have similarly found an excess risk of LBP and sciatic pain in professional drivers [42,58,59,60].…”
Section: Low Back Pain and Sciaticamentioning
confidence: 86%
“…In the same analysis, a summary POR of 1.67 (95% CI 1.25-2.23) was found for 12-month prevalence of sciatic pain in the professional drivers. Earlier meta-analyses have similarly found an excess risk of LBP and sciatic pain in professional drivers [42,58,59,60].Driving involves exposure not only to WBV but also to several ergonomic risk factors which can affect the spine, such as prolonged sitting in a constrained posture (which raises intradiscal pressure) and frequent twisting with a non-neutral trunk position (e.g. looking behind when manoeuvring a fork-lift truck).…”
mentioning
confidence: 99%
“…In the case of female mining vehicle drivers, no previous studies have been conducted that have reported on the prevalence of musculoskeletal symptoms. A review of the available literature has shown that the range of the prevalence of musculoskeletal disorders affecting the lower back among drivers of different vehicles varies widely, from 30% to 85%, between the studies carried out [1,2]. The discrepancies between the studies of professional drivers might be due to differences in the design of the study, the characteristics of the study populations and the definition of LBP outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term occupational exposure to whole-body vibration (WBV) is associated with an increased prevalence of self-reported musculoskeletal symptoms, especially low back pain (LBP) [1][2][3]. The contribution of WBV to those health problems is not fully understood, and it appears that the occurrence and severity of musculoskeletal symptoms is influenced by several factors, such as the nature of exposure to vibration, type of machinery and work process, environmental conditions, and biodynamic and ergonomic factors [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Based on available literature reports, it can be concluded that exposure to high levels of WBV is associated with higher risk of low back pain and sciatica (11). Nevertheless, several researchers investigated whether WBV was feasible for patients with chronic low back pain (19,50).…”
Section: Orthopedicsmentioning
confidence: 99%